NATIONAL DENTAL HEALTH MONTH PROGRAM 2022 SCHOOL HEALTH PROGRAM WITH ITS KINDERGARTEN - Revianti, Syamsulina; Brahmanta, Arya; Agnita Cevanti, Twi; Puspita, Sinta; Khoironi, Emy; Pangabdian, Fani; Widaningsih, Widaningsih; Hanum, Faizah; Listya Paramita, Annisa; Dwi Maharani, Aulia; Paramita, Ayulistya; Iman, Dimas; Rizal, Mohammad Basroni; Anindya Pinasti, Restika; Soesilo, Diana (LPPM Univ. Ibn Khaldun Bogor, 2023)
Dental and oral health in Indonesia is still a health problem that needs attention. The most concerning thing is that as many as 93% of school-age children experience dental and mouth problems. This can be caused by a lack of knowledge and awareness of dental hygiene. One of the efforts made to increase knowledge and awareness of dental hygiene is by holding an educational activity called the